The regulation of post-Communist party politics - Bértoa, Fernando Casal; Biezen, Ingrid van (Routledge studies on political parties and party systems, 2018)
The question of how political parties are, and ought to be, regulated has assumed an increased importance in recent years, both within the scholarly community and among policy-makers and politicians as the state assumes an increasingly active role in the management of, and control over, their behaviour and organisationThis book concentrates on the regulation of political parties in the EU post-communist democracies, and on Bulgaria, Croatia, the Czech Republic, Estonia, Hungary, Latvia, Lithuania, Poland, Slovakia, Slovenia and Romania, in particular. In analysing the various dimensions of party regulation, it builds on the main premises derived from the neo-institutionalist literature in political science, concerning the ways in which the (formal and informal) rules and procedures may influence, constrain or determine the behaviour of political actors. In doing so, it provides a comprehensive overview of the regulation of Eastern European political parties provided by leading experts in the field and casts theoretical and empirical light on the manner in which the constitutional and legal regulation of party organizations and finances have had an impact (or not) on the consolidation of party politics in post-communist Europe since 1989. This text will be of key interest to scholars and students of Political Parties and Behaviour, East European and Post-Communist Politics and Comparative Politics."--Provided by publisher